A Systematic Review of Junior High School Mathematics Curriculum in Indonesia and Australia - Bayu Murti Suryonegoro; Wardono Wardono; Stevanus Budi Waluya; Mulyono Mulyono; Ifan Badra Wijaya (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study analyzes the comparative mathematics curricula between Indonesia and Australia to uncover various aspects of the education systems. The focus is on the similarities and differences between the curricula, systematically examining them in terms of objectives, materials, methods, and assessment, particularly in mathematics. Methodology: This study used a library method with the main data sources coming from 58 articles, 44 books, and 10 official documents in a qualitative descriptive manner. The research data analysis used the Systematic Literature Review method through the following steps: identification, screening, eligibility, and inclusion based on keywords, titles, abstracts, inclusion and exclusion criteria, and referenced literature. Main Findings: The mathematics curriculum in Indonesia and Australia at the Junior High School level is almost the same with a few differences, namely the focus on the profile of Pancasila students and providing more specific mathematical knowledge and skills to support the development numeracy and direct further fields of study in mathematics and other disciplines, so that it can add other aspects or components that researchers have never studied regarding the comparison of the mathematics curriculum in Indonesia and Australia. Novelty/Originality of this study: This analytical study of the comparative study of the Indonesian and Australian mathematics curriculum was conducted by citing various sources, namely articles, journals, official curriculum websites, books, and proceedings articles, thus providing a broader study of further studies on the development of the mathematics curriculum in Indonesia and Australia globally.